MANAJEMEN USAHA PENANGKAPAN IKAN DI PELABUHAN PERIKANAN PANTAI SADENG KABUPATEN GUNUNG KIDUL - TRIMERANI, RESNA ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Boat, machine and fishing gears are major venture capital for the improvement of social status of the fisherman. The fishing effort involves two parties, namely the owner of the means of production and the helmsman and the crews as the the parties who operate the process. Proverbial of two different interests is the beginning of the working relationship which is based on the form of patron-client relationship. This research aims to discover the suitability of the rights and obligations of the owners, the helmsman and the crews